From Gutenberg to the Global Information Infrastructure - Veronica Calderhead (Issues in Science and Technology Librarianship)
The article reviews From Gutenberg to the Global Information Infrastructure : Access to Information in the Networked World. (Digital Libraries and Electronic Publishing Series) Cambridge, Mass. ; London : MIT Press, c2000. 324 p. hardcover $40.00. (ISBN 0-262-02473-X) by Christine L. Borgman.